Development of the REFOCUS intervention to increase mental health team support for personal recovery - Slade, Mike; Bird, Victoria; Le Boutillier, Clair; Grey, Barbara; Larsen, John; Leamy, Mary; Oades, Lindsay; Williams, Julie (Royal College of Psychiatrists, 2015)
Background: There is an emerging evidence base about best practice in supporting recovery. This is usually framed in relation to general principles, and specific pro-recovery interventions are lacking. Aims: To develop a theoretically-based and empirically-defensible new pro-recovery manualised intervention – called the REFOCUS intervention. Method: Seven systematic and two narrative reviews were undertaken. Identified evidence gaps were addressed in three qualitative studies. The findings were synthesised to produce the REFOCUS intervention, manual and model. Results: The REFOCUS intervention comprises two components: recovery-promoting relationships and working practices. Approaches to supporting relationships comprise coaching skills training for staff, developing a shared team understanding of recovery, exploring staff values, a Partnership Project with people who use the service, and raising service user expectations. Working practices comprise: Understanding values and treatment preferences; Assessing strengths; and Supporting goal-striving. The REFOCUS model describes the causal pathway from the REFOCUS intervention to improved recovery. Conclusion: The REFOCUS intervention is an empirically-supported pro-recovery intervention for use in mental health services. It will be evaluated in a multisite cluster randomised controlled trial (ISRCTN02507940).